1992
DOI: 10.1038/sj.bdj.4807987
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary resuscitation skills of dental personnel

Abstract: This study assessed the cardiopulmonary resuscitation (CPR) skills of 25 dental personnel. Theory was tested by multiple choice questionnaire (MCQ) and practical skills assessed using a recording Resusci-Anne manikin. The assessment was based upon the recommendations of the Resuscitation Council of the UK. Seven of the 16 dental students and six of the nine house officers tested passed the MCQ examination. All failed the practical assessment. It is concluded that more emphasis should be placed upon CPR instruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…A sample size of 40 appears to be not very high. Under the circumstance that in Germany 1 year of a class in dental school regularly consists of not more than 50 students, the participants of our study represent the majority of one academic year and, in addition, our results align with other studies from all over the world concerning cardiopulmonary resuscitation in dentistry (14,15,(25)(26)(27)(28)(29)(30)(31).…”
Section: Limitationssupporting
confidence: 87%
“…A sample size of 40 appears to be not very high. Under the circumstance that in Germany 1 year of a class in dental school regularly consists of not more than 50 students, the participants of our study represent the majority of one academic year and, in addition, our results align with other studies from all over the world concerning cardiopulmonary resuscitation in dentistry (14,15,(25)(26)(27)(28)(29)(30)(31).…”
Section: Limitationssupporting
confidence: 87%
“…[10] Chapman and Hussain reported that none of the dental practitioners they evaluated had the practical skills to perform quality CPR. [1112] Arsati et al . in 2010 found that though the occurrence of life-threatening medical emergencies like anaphylaxis, myocardial infarction, cardiac arrest, and cerebrovascular accident is rare in Brazilian dental clinics, dentists are not fully prepared to manage medical emergencies and have insufficient experience training in CPR.…”
Section: Discussionmentioning
confidence: 99%
“…Little has been published about competence of dentists to deal with CPA, or the occurrence of resuscitation emergencies in dental practice (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%